2009
DOI: 10.1042/bst0370102
|View full text |Cite
|
Sign up to set email alerts
|

RecA family proteins in archaea: RadA and its cousins

Abstract: Recombinases of the RecA family are essential for homologous recombination and underpin genome stability, by promoting the repair of double-stranded DNA breaks and the rescue of collapsed DNA replication forks. Until now, our understanding of homologous recombination has relied on studies of bacterial and eukaryotic model organisms. Archaea provide new opportunities to study how recombination operates in a lineage distinct from bacteria and eukaryotes. In the present paper, we focus on RadA, the archaeal RecA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
68
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 41 publications
2
68
0
2
Order By: Relevance
“…HR is universally catalyzed by recombinases, i.e., RecA in bacteria, Rad51 in eukaryotes, and RadA in archaea (1,2). HR recombinases promote the exchange of homologous DNA strands, a prerequisite for which is the formation of a complex between ssDNA and the recombinase called the "presynaptic filament."…”
mentioning
confidence: 99%
“…HR is universally catalyzed by recombinases, i.e., RecA in bacteria, Rad51 in eukaryotes, and RadA in archaea (1,2). HR recombinases promote the exchange of homologous DNA strands, a prerequisite for which is the formation of a complex between ssDNA and the recombinase called the "presynaptic filament."…”
mentioning
confidence: 99%
“…Euryarchaeal RadB and crenarchaeal stRadC2 are known to inhibit RadA recombination activity, which has enriched our knowledge on crenarchaeal DNA recombination. In addition, stRadC2 interacts with Hjc and facilitates the resolution of Holliday DNA junctions, which is more similar to its eukaryotic equivalents [3][4][5][6] than to its euryarchaeal ones [9,10]. At the late stages of DNA recombination, the cell ends DNA repair and starts normal metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, sequence alignment showed that some of these proteins, for instance, SSO2452 and SSO1861 in S. solfataricus, and ST0579 and ST1830 in S. tokodaii were more similar to the KaiC-like proteins than to any known RadA/Rad51 paralog found throughout archaea and eukarya. Therefore, these proteins were named RadC by Haldenby [9]. However, the real roles of RadC proteins in archaea remain unclear.…”
mentioning
confidence: 99%
See 2 more Smart Citations